Teacher Agency in Reproducing Translanguaging Practices as Social Justice Strategy to Decolonize ELT - Harjuli Surya Putr (IAFOR Journal of Education)
Teachers are vital internal pioneers who can make changes in their own classroom by developing an enhanced sense of agency. In multilingual classrooms, teacher agency is the capacity of language teachers to perform constructively for supporting students’ linguistic diversity equitably. This study uncovers the potential strategy of teacher agency to create translanguaging space in empowering EFL students’ semiotic repertoire toward linguistic justice and inclusion to resist a raciolinguistics ideology. Drawing upon the translanguaging and agency conceptual framework, data were collected from classroom observations and video-stimulated-recall-interview of teacher’s pedagogical translanguaging practices in an EFL classroom in Indonesia. Multimodal Conversation Analysis triangulated with the video-stimulated-recall-interview data analyzed applying Interpretative Phenomenological Analysis was used as a technique of data analysis. Findings revealed three key themes that trace the teacher agency in constructing translanguaging practices in EFL classroom as follows: (1) adjusting language use to suit the students’ English competence as a process to guide and help them in the classroom discussion, (2) empowering the relational and critical dispositions, drawing from all linguistic resources to help students negotiate various communicative contexts for inclusive and meaningful communication, (3) providing that all students get more equitable and inclusive education to freely employ their semiotic repertoire. The findings demonstrate how the enactment of teacher translanguaging agency employed in turn influenced students’ agency to demonstrate transformative participation in classroom activities.